Prevalence of calreticulin exon 9 indel mutations in vascular risk patients - Jaeger, Thomas; Muendlein, Axel; Hodaie, Jasmin; Untergasser, Gerold; Steurer, Michael; Saely, Christoph H.; Drexel, Heinz; Lang, Alois H. (Thrombosis research, 2016)
Acquired JAK2 as well as calreticulin (CALR) mutations are involved in the development of Philadelphia-negative myeloproliferative neoplasms (MPN). We previously showed that the JAK2 V617F mutation could also been found in coronary patients and in patients with peripheral arterial disease (PAD). However, prevalence of CALR mutations is unknown in vascular risk patients and its evaluation subject of the present study. We determined the prevalence of CALR exon 9 indel mutations in a cohort of 1052 angiographied coronary patients, including 141 patients with PAD, and, additionally, 86 patients with PAD, but without coronary angiography. CALR mutation analysis was performed using PCR fragment analysis and JAK2 V617F mutation analysis with allele-specific real-time PCR. From included 1138 patients, 18 individuals were tested positive for the JAK2 V617F mutation. CALR exon 9 mutations were not detected in any of our patients. We conclude that CALR exon 9 mutations are infrequent in vascular risk patients. Routine testing for the presence of CALR mutations is not recommended for unselected patients with vascular disease. Future studies are warranted to define a putative pathologic role of CALR mutations in patients without MPN. •We examined the prevalence of CALR mutations in 1138 vascular risk patients.•The JAK2 V671F mutation was present in 1.6% of included patients.•None of included patients carried a CALR mutation.